Necesidad de implementar un inciso en el art 282 del COIP a quienes incumplan decisiones legitimas de autoridad competente en situaciones de emergencia sanitaria. - Masache Quinche, Pablo Guillermo (2023)
The present Curricular research work is entitled "need to implement a subsection in article 282 of the COIP to those who fail to comply with legitimate decisions of the competent authority in situations of health emergency". Whose interest arises from the pandemic caused by SARS-CoV-2 better known as COVID-19. Disease that originated in the city of Wuhan-china, at the end of December 2019, in which not only our country was affected, but the entire world population, seriously affecting the lives of people, causing economy of each country is affected and worst of all, the loss of many human lives. The World Health Organization determines that a health emergency is declared when a serious disease occurs in an unusual, sudden, unexpected way, whose affectation can be not only locally but also internationally due to its rapid spread. States must act quickly and in a timely manner to guarantee the life and health of their citizens, particularly in our country the necessary measures were taken to deal with this disease, measures such as the declaration of a health emergency within the national territory, biosecurity measures such as social distancing, constant cleaning of hands, the use of masks, but above all the use of decrees, such as the state of emergency in which some rights such as freedom of movement, prohibition of meetings, etc., were suspended. People who fail to comply with the decisions that were issued by the Executive through decrees to somehow stop the massive contagion of the virus within the national territory, were liable to be prosecuted for the crime of non-compliance with legitimate decisions of the competent authority, stipulated in the art. 282 of the Comprehensive Organic Criminal Code. In view of which, I consider that not all behaviors or disobedience that occurred in the health emergency were susceptible to being punished under this crime, since most people were unaware of the legal consequences of failing to comply with any order of competent authority, likewise the majority of people live from day to day, so they found themselves in need of going out to look for the economic resources that allow them to bring food to their homes. In order for people's conduct to be prosecuted, it is important to have regulations that indicate such conduct is prohibited, as indicated by constitutional principles such as: the principle of legality, the principle of proportionality, the principle of necessity, etc. that we will analyze in detail within this paper, and other issues of equal importance such as the legitimate decision, state of exception, criminality, which refers to the adequacy of the conduct to what is 5 described in the criminal type. It is evident that this article 282 of the COIP presents a problem of interpretation, since it is not specific to what type of conduct it refers to and which is the competent authority that issues it, failing to comply with legal certainty by stating that all regulations must be clear. An inconvenience and no less important that the application of this crime can generate in health emergency situations is prison overcrowding, a problem suffered by most of the country's detention centers. According to the PRIMICIA digital news portal, with data obtained by the SNAI, currently 58% of prisons suffer from overcrowding, despite the fact that the percentage has decreased compared to previous years, it is still a danger to health and security of those who are deprived of their liberty, even more so in pandemic circumstances such as covid-19, there is the possibility of a greater contagion when being in reduced physical spaces, thus hindering all means of preparation, prevention and response that we must have in the face of a rapidly spreading disease. In the development of this research work, a series of methods and materials were used that have allowed it to be carried out, through surveys and interviews directed to legal professionals in the city of Loja, with clear and concise criteria, the same that served to verify the objectives and the foundation of the legal reform to the Comprehensive Organic Criminal Code in order that people who fail to comply with a decision of a competent authority in a declaration of health emergency are not deprived of their liberty, more either be financially sanctioned, preventing the overcrowding in prisons from increasing and the resources obtained for disobeying any decision from being used for the expenses involved in a health emergency, either by providing biosafety implements to hospitals or even for the acquisition of vaccines for the population.